2008
DOI: 10.1093/jmedent/45.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Vector Competence of Selected African Mosquito (Diptera: Culicidae) Species for Rift Valley Fever Virus

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 24 publications
4
114
2
Order By: Relevance
“…The flooding of dambos induces the hatching of transovarially infected Aedes mcintoshi mosquito eggs that are dormant in the soil, producing infected adult females in 7-10 days that can transmit RVF virus to domestic animals (1,22,25). After a blood meal, the Aedes mosquitoes will lay infected eggs on moist soil at the edge of mosquito habitats, but appear to not be an efficient secondary vector of the virus between infected and noninfected domestic animals and humans (25,26). However, Culex species mosquito vectors subsequently colonize these flooded dambos and, with a delay of several weeks, large populations of these mosquitoes emerge and efficiently transmit the virus from domestic animals, which amplify the virus, to noninfected domestic animals and humans (22,25,26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flooding of dambos induces the hatching of transovarially infected Aedes mcintoshi mosquito eggs that are dormant in the soil, producing infected adult females in 7-10 days that can transmit RVF virus to domestic animals (1,22,25). After a blood meal, the Aedes mosquitoes will lay infected eggs on moist soil at the edge of mosquito habitats, but appear to not be an efficient secondary vector of the virus between infected and noninfected domestic animals and humans (25,26). However, Culex species mosquito vectors subsequently colonize these flooded dambos and, with a delay of several weeks, large populations of these mosquitoes emerge and efficiently transmit the virus from domestic animals, which amplify the virus, to noninfected domestic animals and humans (22,25,26).…”
Section: Resultsmentioning
confidence: 99%
“…After a blood meal, the Aedes mosquitoes will lay infected eggs on moist soil at the edge of mosquito habitats, but appear to not be an efficient secondary vector of the virus between infected and noninfected domestic animals and humans (25,26). However, Culex species mosquito vectors subsequently colonize these flooded dambos and, with a delay of several weeks, large populations of these mosquitoes emerge and efficiently transmit the virus from domestic animals, which amplify the virus, to noninfected domestic animals and humans (22,25,26). By using information gained from previous RVF outbreaks (2, 12, 25, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by studies of RVFV although no significant decrease in detection has been observed from adult pools [94]. Therefore the use of pooled larvae in previous studies may have limited the potential to detect virus and caused the negative results [42,73,95]. If the testing of pooled larvae is considered necessary, a combination of assays can be used.…”
Section: Detection Methodsmentioning
confidence: 95%
“…Infection can be performed orally via feeding on a viraemic animal or artificial blood meal, or intrathoracic inoculation, by injecting virus through a soft area of cuticle in the thorax directly into the haemocoel. Inoculation bypasses the midgut resulting in near 100 % infection rates, circumventing problematic feeding rates [42]. It can be performed directly with quantified…”
Section: Laboratory Studiesmentioning
confidence: 99%
See 1 more Smart Citation